Investigation on jet diffusion mechanism with applications to enhancing efficiency in forming directional fractures. (1st January 2023) - Tang, Jiren; Chen, Long; Liu, Wenchuan; Zhang, Huali; Wang, Junxin; Liu, Qi
Abstract: The jet-based technologies were introduced in roof directional pre-cutting, which is one of the critical technologies in the no-pillar mining method without excavating mining roadways. Based on the laboratory and field experiments, both directional hydraulic fracturing and hydraulic slotting technologies were able to form the directional fractures, and their performances were affected by cutting efficiency. Jet diffusion was affected by flow instabilities and had effects on cutting efficiency. To further enhance the cutting efficiency, numerical simulations based on the modified cavitation and turbulence models were performed to elucidate the jet diffusion mechanism, and a new type of slotter is designed to address the problems of jet diffusion and the short service life of the current original slotter. Cavitation-vortex interaction was observed in the slotter and worked together with turbulence to account for the jet diffusion. The new slotter weakened the instabilities induced by both turbulence and bubble collapse/burst, and thus suppressed the diffusion disintegration process of the jet. Compared with the conventional slotter, the diffusion angle of the new slotter is reduced by 50%, and the slotting performance is improved by 30%. The present study serves as a supplement to channel optimization, contributing to the further enhancement of pre-cutting efficiency. Highlights: Hydraulic techniques have the advantage of forming directional fractures accurately. Jet diffusion impaired the slotting performance and pre-cutting efficiency. A modified model was used to elaborate the jet diffusion mechanism. New slotters weaken the flow instability and enhance the slotting performance by 30%. A conveyor was developed independently to enhance the roof pre-cutting efficiency.